Enhancement of the crystallization and biocompatibility of poly(TMC-b-(LLA-ran-GA)) by poly(lactide) stereocomplex. Issue 41 (8th October 2019) - Fan, Tiantang; Qin, Jingwen; Lin, Shengli; Ye, Wuyou; Li, Jiafeng; Zhang, Qin; Gong, Li; Liu, Dongyang; Fan, Zhongyong
Abstract : A series of poly(1, 3-trimethylene carbonate- b -(l -lactide- ran -glycolide)) (PTLG) with the three-armed PDLA and PLLA stereoblock copolymer (sc-PLA) acting as the nucleating agent was prepared via the solution-casting method. Abstract : A series of poly(1, 3-trimethylene carbonate- b -(l -lactide- ran -glycolide)) (PTLG) with the three-armed PDLA and PLLA stereoblock copolymer (sc-PLA) acting as the nucleating agent was prepared via the solution-casting method. The effects of the incorporation of various amounts of sc-PLA crystallites on the crystallization behavior and mechanical properties of the PTLG matrix were characterized via DSC, WAXD, POM, and mechanical measurements. The results exhibited that the sc-PLA crystallites obviously enhanced the crystallization rate of the PLLA segments in the PTLG matrix. The results from the investigation of non-isothermal crystallization behavior showed that the crystallization process was significantly accelerated with the sc-PLA crystallites, and with an increase in the content of sc-PLA crystallites, the crystallization temperature shifted to 123.5 °C compared to that of the pure PTLG matrix. The results from the isothermal crystallization behavior study showed that the relative degree of crystallinity ( X t ) gave a typical S-shape curve and the half-time of crystallization ( t 0.5 ) decreased with an increase in the amount of added sc-PLA crystallites. The crystallization accelerating effects mainly depended on the preeminent nucleation ability of the sc-PLA crystallites, which was proven by POM measurement. The mechanical measurement results showed that with the introduction of sc-PLA crystallites, the tensile strength of the blends was remarkably improved from 21.1 to 85.8 MPa. Furthermore, the biocompatibility of PTLG/sc-PLA was evaluated using the CCK-8 assay and live/dead staining. The results indicated that PTLG/sc-PLA presented very low cytotoxicity. Therefore, the low crystallization rate of the PLLA segments in the PTLG matrix can be largely improved by using sc-PLA crystallites as nucleating agents, and PTLG/sc-PLA blends possess good cytocompatibility and are expected to be used as bioresorbable vascular stents in the bio-medical field.